AB0177 Simultaneous blockade of the CD40/CD40L and NF-κB pathways improving therapy effect on arthritic rats. (23rd January 2014) - Fan, P.; He, L.; Pu, D.; Zhou, W.; Sun, Y.
Abstract : Background: Rheumatoid arthritis (RA) is one of chronic autoimmune diseases that harm the human health for a long time. The pathogenesis of RA is still unknown, which refers to several aspects of the immune system. Especially, the aberrant activation of the lymphocytes and the NFκB dependent nonspecific inflammatory response are the two main points of joint inflammatory damage in RA. CD40/CD40L is the key co-stimulated molecular in the recognition and activation of the T cells. IκBα can suppress the inflammatory response and injury of joint synovium by cytokine at the key point by inhibiting the NFκB signaling. Objectives: In this study, we used CD40LIg-IRES2- IκBα co-expressing adenovirus vector to transfect the synovium tissue of arthritic rats to investigate the genes expression as well as the effect on the arthritic rats. In addition, we will compare the therapeutic effect of the co-expression gene adenovirus and the single gene adenovirus vector, to explore the potential gene therapy for RA. Methods: Construction of pAdCD40LIg, pAdIκBα and pAdCD40LIg-IRES2-IκBα adenovirus vector had completed. Wistar rats were rendered arthritic by multi-subcutaneous injection of complete Freund's adjuvant. Arthritic rats were divided into four groups: group A with distal joint cavity injection of sterile water as control (n=5); group B with injection of pAdCD40LIg vector (n=5); group C with pAdIκBα vector injection (n=5); and group D with injection of pAdCD40LIg-IRES2-IκBα vector (n=5). Therapy effects were measured by the method of arthritis index score of rats. The levels of TNF-α, IL-2, IL-6 in synovial fluid collected by joint puncture were measured by ELISA methods 21 days after treatment. Results: The mean arthritis index score of rats in group D was significantly lower than those in other three groups (P<0.05). The index in group B and C were significantly lower than that in group A (P<0.05). The rats in group D had the lowest TNF-α, IL-2 and IL-6 levels in synovial fluid followed by group C, B and A (P<0.05). Conclusions: The expression CD40LIg and IκBα can effectively inhibit inflammatory reaction of arthritic rats. Simultaneous expression CD40LIg and IκBα can improve the therapeutic effect by synergistic effect. References: Munroe ME, Bishop GA. A costimulatory function for T cell CD40. J Immunol, 2007, 178(2):671-682. Makarov SS. NF-κB in rheumatoid arthritis:a pivtoal regulator of inflmmation, hyperplasia and tissue destruction. Arthritis Res, 2001, 3(4):200-206. Malfait AM, Williams RO, Malik AS, et al. Chronic relapsing homologous collagen-indueed arthritis in DBA/1 mice as a model for testing disease-modifying and remission-inducing therapies. Arthritis Rheum, 2001, 44(5):1215-1224 Disclosure of Interest: None Declared